2023
DOI: 10.3389/fmicb.2023.1040605
|View full text |Cite
|
Sign up to set email alerts
|

Role of seed infection for the near and far distance dissemination of wheat blast caused by Magnaporthe oryzae pathotype Triticum

Abstract: Magnaporthe oryzae pathotype Triticum (MoT) is a devastating fungal phytopathogen causing wheat blast disease which threatens wheat production particularly in warmer climate zones. Effective disease control is hampered by the limited knowledge on the life cycle, epidemiology, and pathogenicity of MoT. Since MoT mainly infects and colonizes the inflorescences of wheat, infection, invasion routes and colonization of MoT on wheat ears and in wheat seeds were investigated in order to assess potential seed transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…The Magnaporthe oryzae Triticum (MoT) strain was obtained from Luciana Macis (Georg‐August‐University Göttingen, Plant Pathology and Crop Protection Section, Göttingen, Germany). According to previously described methods (Surovy et al, 2023b), MoT was inoculated on fresh PDA medium and propagated at 21°C for 10 d. Next, 5 mL phosphate buffer (137 mM NaCl, 2.7 mM KCl, 10 mM Na 2 HPO 4 and 1.8 mM KH 2 PO 4 ) containing 0.01% Tween‐20 solution was used to collect the spores. Then, the suspension was further filtered through a two‐layer sterile cheesecloth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Magnaporthe oryzae Triticum (MoT) strain was obtained from Luciana Macis (Georg‐August‐University Göttingen, Plant Pathology and Crop Protection Section, Göttingen, Germany). According to previously described methods (Surovy et al, 2023b), MoT was inoculated on fresh PDA medium and propagated at 21°C for 10 d. Next, 5 mL phosphate buffer (137 mM NaCl, 2.7 mM KCl, 10 mM Na 2 HPO 4 and 1.8 mM KH 2 PO 4 ) containing 0.01% Tween‐20 solution was used to collect the spores. Then, the suspension was further filtered through a two‐layer sterile cheesecloth.…”
Section: Methodsmentioning
confidence: 99%
“…However, it was found that linear lipopeptides from a marine B. subtilis strain inhibit the growth of MoT (Chakraborty et al, 2020). Moreover, volatile organic compounds from B. subtilis and B. velezensis suppressed MoT in vitro and in vivo (Surovy et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…MoT fungal pathogen BTGP 6(f) was isolated from blast-infected wheat ear [ 48 ] and grown on V8 agar (V8A) following the protocol described by Surovy et al [ 49 ]. The conidial suspension was prepared from 7-d-old MoT cultures by adding 0.01% sterile Tween 20 solution (10 mL) per plate.…”
Section: Methodsmentioning
confidence: 99%